Pengembangan Media Pembelajaran Interaktif Untuk Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan - Nur Budi Nugraha (UNIVERSITAS STEKOM, 2024)
Physical Education, Sports and Health are subjects that equip students with physical skills, health understanding and healthy living habits. This subject not only emphasizes the development of physical fitness, but also the formation of character, discipline and teamwork. Traditional teaching methods often face challenges in maintaining student interest and participation. Students who are used to digital technology feel that conventional methods are less interesting and irrelevant to their digital world. This research uses the waterfall method and aims to develop interactive learning media that integrates various elements such as animation, video tutorials, motion simulations and interactive quizzes. The results of the research produced interactive learning media with validation results from material and media experts showing a high level of feasibility, with an average score of 85%, exceeding the minimum criteria of 75%. Student responses were very positive, with 87% stating that this media increased their understanding and interest in learning.